2019
DOI: 10.3390/cells8050418
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Patient-Derived Xenograft Models for Preclinical Studies of Anti-Cancer Drugs in Solid Tumors

Abstract: Patient-derived xenograft (PDX) models are used as powerful tools for understanding cancer biology in PDX clinical trials and co-clinical trials. In this systematic review, we focus on PDX clinical trials or co-clinical trials for drug development in solid tumors and summarize the utility of PDX models in the development of anti-cancer drugs, as well as the challenges involved in this approach, following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Recently, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 123 publications
(188 reference statements)
2
81
0
3
Order By: Relevance
“…In contrast, SCID/beige mice, Rag2 KO mice, and Rag2 KO/Jak3 KO mice were used only by 2 facilities (11.8%), one facility (5.9%), and one facility (5.9%), respectively. These were similar to the trend of the mouse strains used in recent PDX models found in a literature search 8 . As shown in Table , the majority of the respondents used either nude mice because of the cost and ease of handling or NOG or NSG mice because they are the most immune deficient, allowing for more efficient engraftment of human‐derived cancer tissue.…”
Section: Mouse Strains Used In Pdx Models and Housing Environments Fosupporting
confidence: 75%
“…In contrast, SCID/beige mice, Rag2 KO mice, and Rag2 KO/Jak3 KO mice were used only by 2 facilities (11.8%), one facility (5.9%), and one facility (5.9%), respectively. These were similar to the trend of the mouse strains used in recent PDX models found in a literature search 8 . As shown in Table , the majority of the respondents used either nude mice because of the cost and ease of handling or NOG or NSG mice because they are the most immune deficient, allowing for more efficient engraftment of human‐derived cancer tissue.…”
Section: Mouse Strains Used In Pdx Models and Housing Environments Fosupporting
confidence: 75%
“…Drug-adapted cancer cell lines are, like every model system, associated with specific advantages and limitations. Models including primary cancer cell cultures, three-dimensional cell (co-) culture systems, tumour-derived organoids, and animal models better reflect certain aspects of tumour growth such as intra-tumour heterogeneity, three-dimensional architecture, cancer cell interaction with the cancer microenvironment, and/ or metastatic behaviour [105][106][107][108][109][110][111][112][113][114] . Such models can be used to study processes that cannot be studied in cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Patient-derived xenograft (PDX) models are valuable tools for preclinical cancer research studies (1). Several studies have reported that patient-derived glioma stem cells (GSCs) maintain the phenotype and genotype characteristics of the original tumors (2)(3)(4), and GSC-derived xenografts recapitulate the distinctive cytological hallmarks and diverse histological variants of the original tumors (5).…”
Section: Introductionmentioning
confidence: 99%